Edukasi Kesehatan Ibu Hamil dalam Pencegahan Stunting di Kampung KB Bina Kencana RT 32 Kelurahan Lebak Bandung Kota Jambi - Tiwi, Laida Sanilpa; Nurbaiti, Nurbaiti; Indrawati, Iin (Jurnal Abdimas Kesehatan (JAK), 2025)
Pregnant women play an important role in preventing stunting because the nutritional status of the mother during pregnancy greatly affects the growth and development of the fetus. Poor nutrition during pregnancy, growth period and early life of the child can cause the child to become stunted. Efforts to prevent stunting are through a family approach by conducting regular pregnancy check-ups at health services, and monitoring child growth and development through Posyandu cadres. Routine ANC visits can detect and prevent risk factors for stunting by providing services on maternal health status, immunization, nutrition and breastfeeding counseling. The purpose of community service activities is to realize the Tri Dharma of Higher Education in helping to improve the standard of living and welfare of the community for the prevention of stunting by conducting regular pregnancy check-ups and meeting nutritional intake during pregnancy. This activity was carried out on November 23, 2022 in the Bina Kencana RT 32 KB village, Lebak Bandung Village, with 15 participants. The implementation method was with lectures, discussions and questions and answers. The media used were leaflets and infocus. Based on the results of the pre-test and post-test, it was known that 6 pregnant women had good knowledge and after being given education, the results obtained were that 15 pregnant women had good knowledge. Therefore, efforts to prevent stunting need to be focused on improving maternal nutrition and health from preconception to pregnancy.